Elite Capture, Institutional Performance and the 2015 National Electoral Outcomes in Nigeria - SHA , Dung Pam (Socialscientia: Journal of Social Sciences and Humanities, 2021)
A major concern of all stakeholders from the differentiated political spectrum in Nigeria has been the production and distribution of Permanent Voters Cards (PVCs). A strategic error was made by INEC in the production and distribution of the PVCs as many voters did not vote in the 2015 national elections on account of their non-possession of the cards. The production and the distribution commenced late but specifically, the distribution was first designed to be at the ward and later local government levels which posed severe challenge for voters to collect their cards at these levels. Voters are used to collecting their voter’s cards at the polling units where registration normally takes place. INEC statistics shows that 56,431,255 cards representing 81.98% of registered voters were distributed, but a large percentage of these cards did not get to the actual owners. There was an elite capture of the distribution process which ultimately affected the performance of INEC in reaching the electorates with their only instrument of electoral mandate. Some of the PVCs were hidden, diverted and sold and these transactions with political and economic motives were perpetrated by political elites within and outside INEC. We argue that when state institutions make strategic errors in programming either as a result of pressure from vested interests, or unforeseen situations, they (i) create avenues for elite capture and in this case, the capture of the distribution function and this adversely affected the effectiveness of INEC and therefore the quality of electoral outcomes in the country (ii) these institutions are bound to incur huge losses including higher transaction cost in rectifying the errors and block areas of elite capture. Early institutional programming is needed to ensure Continuous Voter Registration and the production of electoral materials. A reform is needed to strengthen the independence of INEC thereby weakening future elite resolve at capturing such processes; and a revisiting of the production of new PVCs to ensure that all illegible voters possess their PVCs. This will ensure the protection of electoral mandates and the strengthening of democracy.